The Role Of Transformative Leadership In The 21st Century: Meaning The Problematics Of The Pancasila Democracy System - Rustan Effendi, Julius; Iswahyudi, Didik; Samapati, Cevin (JURNAL TAPIS, 2024)
Transformative leadership, as an evolving paradigm in the context of the 21st century, offers unique insights into understanding and addressing the current challenges related to democracy. Transformational leadership in the Pancasila democracy in Indonesia, particularly among students, is not without challenges. One of the main obstacles faced is resistance to the old political culture, which tends to be authoritarian. Students, who should be agents of change, often get trapped in hierarchical thinking and are less open to change. This political culture hinders the spirit of inclusive and democratic leadership. This article aims to explore the role of transformative leadership in the 21st century in interpreting Pancasila democracy and addressing various issues arising in the context of democracy within student organizations. Through transformative leadership, this article offers solutions based on empowerment, active participation, and the development of members' capacities. Transformative leadership fosters an inclusive environment where individuals' voices are valued. This creates a strong foundation for resolving conflicts, building trust, and promoting sustained engagement. This article uses qualitative research with a descriptive approach. Transformative leadership has great potential to serve as a facilitator in addressing the democratic issues of the contemporary era. Through this approach, it is hoped that student organizations can build a stronger foundation for a more inclusive, dynamic, and sustainable democracy.